A pilot randomized controlled trial comparing the effectiveness of different spaced learning models used during school examination revision: the SMART Spaces 24/10 model - O’Hare, Liam; Stark, Patrick; Gittner, Alastair; McGuinness, Carol; Thurston, Allen; Biggart, Andy (Frontiers in Education, 2023)
Introduction The main aim of this pilot study was to compare the efficacy of using different spaced learning models during school examination revision on pupil attainment. Spaced learning is using intervals between periods of learning rather than learning content all at one time. Methods Three spaced learning models with different inter-study intervals (ISI’s) were co-designed by teachers and researchers using research evidence and practice knowledge. A pilot randomized controlled trial compared the three ISI models against control groups in 12 UK secondary schools’ science classes (pupil n = 408). The effects on attainment of each model were assessed using pre and post-tests of science attainment. Results The results showed that all three models were feasible for use in a classroom. The spacing model using ISI of 24-h spaces between and 10-min spaces within revision sessions was the only significant one for improving attainment against a control group (effect size d = 0.19, p = <0.05). The study also found that student engagement with the spaced learning program was a statistically significant predictor of increased pupil attainment. Discussion The study demonstrates the potential benefits of applying spaced learning to exam revision, with the most optimal ISI model found to be the SMART Spaces 24/10 model.